2011
DOI: 10.1111/j.1440-0960.2011.00800.x
|View full text |Cite
|
Sign up to set email alerts
|

Tele-assessment of Psoriasis Area and Severity Index: A study of the accuracy of digital image capture

Abstract: We demonstrate that PASI scores can be determined with moderate to good accuracy by dermatologists using standardized digital images. Our results imply the implementation of a tele-PASI service may be a practical and effective adjunct to the dermatological care of patients with severe psoriasis where incapacity or distance prevent the realisation of face-to-face consultations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 14 publications
2
46
0
1
Order By: Relevance
“…Singh and colleagues study that was published in 2011, reported a good agreement between face to face visit and digital images. 4 The results of this study encouraged the application of teledermatology approach in psoriasis management. In 2012, the first trial emerged for Assessment of psoriasis respond to treatments can be measured by various tools such as the DLQI and PASI scores; however, PASI is the widely accepted tool for disease control.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Singh and colleagues study that was published in 2011, reported a good agreement between face to face visit and digital images. 4 The results of this study encouraged the application of teledermatology approach in psoriasis management. In 2012, the first trial emerged for Assessment of psoriasis respond to treatments can be measured by various tools such as the DLQI and PASI scores; however, PASI is the widely accepted tool for disease control.…”
Section: Discussionmentioning
confidence: 61%
“…Finally, we included seven studies for this systematic review (Table 1 and Figure 1). 4,6,8,[12][13][14][15] There were four RCTs, two prospective cohorts and one case series study. The total sample size was 596 with a male prevalence of 53%.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of telemedicine in the evaluation and management of psoriasis in clinical care settings has been documented . Additionally, previous studies have demonstrated that telemedicine‐based clinical assessments using standardized digital photographs are comparable with in‐person assessments in several dermatological conditions …”
Section: In‐person Vs Photographic Psoriasis Area and Severity Indexmentioning
confidence: 99%
“…Therefore more attention and resources should be given to the collection of good standardized images, as it is a crucial investment for any future research using artificial intelligence. Singh et al 19 already showed that bad photograph quality impacted a physician's image-based psoriasis assessment. Our results on the images with only 25% of the original image resolution show that image quality influences results in machine learning as well.…”
Section: Implications For Practicementioning
confidence: 99%